2014
DOI: 10.1038/bonekey.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplements with or without calcium to prevent fractures

Abstract: Vitamin D deficiency is associated with fractures. This relationship is biologically plausible. The results of 19 randomized clinical trials with vitamin D with or without calcium show varying results: a decreased fracture incidence in 7, neutral in 10 trials, whereas 2 trials with a high dose of vitamin D once per year showed an increased fracture incidence. In three out of four well-powered trials that used recommended doses of vitamin D 700-1000 IU per day, vitamin D supplementation did not significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 56 publications
0
36
0
3
Order By: Relevance
“…Numerous clinical trials and meta-analyses have therefore been performed to investigate the effect of vitamin D supplementation with or without calcium on fracture incidence. In general, the effect of vitamin D alone compared with placebo had no effect on fracture risk, whereas meta-analyses on the combination of vitamin D and calcium were inconclusive showing a 12-26% reduction in fracture risk in some meta-analyses, but no effect in others (264). Several factors may explain these inconsistencies.…”
Section: Human Studiesmentioning
confidence: 71%
See 1 more Smart Citation
“…Numerous clinical trials and meta-analyses have therefore been performed to investigate the effect of vitamin D supplementation with or without calcium on fracture incidence. In general, the effect of vitamin D alone compared with placebo had no effect on fracture risk, whereas meta-analyses on the combination of vitamin D and calcium were inconclusive showing a 12-26% reduction in fracture risk in some meta-analyses, but no effect in others (264). Several factors may explain these inconsistencies.…”
Section: Human Studiesmentioning
confidence: 71%
“…Below 10 ng/ml 25OHD there is a deficit in substrate leading to lower serum1,25(OH) 2 D levels and a decrease in intestinal calcium absorption (325). Extensive clinical experience and some randomized control trials indicate that daily intake of 400 IU vitamin D 3 is sufficient to prevent this type of rickets in children (55,264). In adults, clinical vitamin D-related osteomalacia is usually found in individuals with low sun exposure or in patients with impaired intestinal vitamin D absorption as part of intestinal fat malabsorption, like after bariatric surgery or with inflammatory bowel disease (395).…”
Section: Human Studiesmentioning
confidence: 99%
“…4). This conclusion is based on several cross-sectional and long-term observational studies as reviewed in more than 14 meta-analyses [6,43,55]. These data however do not prove causality as a low vitamin D status may also be related to osteoporosis and fractures due to unrelated confounding factors or "reverse causality", i.e.…”
Section: Osteoporosis: Role Of Vitamin D Supplementationmentioning
confidence: 84%
“…In these children with vitamin D deficiency, the serum concentrations of 25-hydroxyvitamin D (25OHD) are usually well below 10 (and mostly below 5) ng/ml, in line with the threshold for 25OHD needed for active intestinal calcium absorption [6,42]. To prevent this type of rickets in children, it is generally accepted that daily intake of about 400 IU (10 ug) of vitamin D 3 is sufficient, as supported by extensive clinical experience and some randomized controlled trials (RCTs) [6,43]. There is less agreement on the use of vitamin D supplementation in pregnant or lactating mothers to prevent rickets in their offspring as only very high doses of vitamin D are able to increase the concentration of vitamin D in mother's milk [44].…”
Section: Rickets: Bone Pathology Of Children With Lack Of Vitamin D Amentioning
confidence: 98%
“…Most RCT compared vitamin D-fortified with unfortified dairy products in participants with a high vitamin D status, and therefore we cannot conclude whether vitamin D added to dairy products is more beneficial for bone health. However, several meta-analyses (71,72) that showed that the combination of Ca and vitamin D is better than either of them alone underscore the importance of dairy products as a vehicle for vitamin D fortification. In general, further study on bone health is needed in other ethnicities than Chinese and Caucasians, and in men.…”
Section: Resultsmentioning
confidence: 99%